2009
DOI: 10.1002/em.20506
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome abnormalities during porcine oocyte aging

Abstract: Centrosomes are critically important for maintaining meiotic spindle integrity in the meiosis II (MII) stage where oocytes are arrested in most mammalian species before fertilization takes place. In women of advanced ages or during in vitro fertilization (IVF) procedures, aneuploidy is frequently seen as a result of oocyte aging, which is strongly related to centrosome instability. Abnormal distribution of centrosomes and microtubules has been reported in aging human and mouse oocytes. This study reports the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The MI and MII spindles are highly susceptible to environmental influences (reviewed in ) including aging (Miao et al 2009a(Miao et al , 2009b Miao et al (2009b)). It has generally been observed that in oocytes affected by aging or by environmental factors, centrosomes disintegrate from the MII spindle poles followed by loss of microtubule tension, loss of microtubule connections to the kinetochores, and MII spindle deterioration (reviewed in Miao et al (2009b)).…”
Section: Oocyte Centrosomes and Centrosomal Pathologies Associated Wimentioning
confidence: 99%
“…The MI and MII spindles are highly susceptible to environmental influences (reviewed in ) including aging (Miao et al 2009a(Miao et al , 2009b Miao et al (2009b)). It has generally been observed that in oocytes affected by aging or by environmental factors, centrosomes disintegrate from the MII spindle poles followed by loss of microtubule tension, loss of microtubule connections to the kinetochores, and MII spindle deterioration (reviewed in Miao et al (2009b)).…”
Section: Oocyte Centrosomes and Centrosomal Pathologies Associated Wimentioning
confidence: 99%
“…In phase II, this bipolar configuration could be stabilized, thereby reducing the distance between 2 points of PCMs and affording maturation competence to the oocytes. However, it has been reported that metaphase spindle in over-matured oocytes exhibit characteristic patterns of centrosome deterioration and frequently display tri-or multipolar spindle poles; these oocytes could not be fertilized, or alternatively, the fertilized oocytes exhibited aneuploidy or developmental abnormalities [48,49]. It has been shown that MAPK activities gradually decrease in aging oocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, increasing evidence also supports a link between centrosome dysfunction and senescence, suggesting that this organelle could directly or indirectly play a role in aging. Aged porcine oocytes exhibit a loss of γ-tubulin and NuMA, critical components of the PCM at the meiotic spindle, giving rise to abnormal and disorganized spindles [31]. Similarly, microtubules are gradually lost from the spindle of aged mouse oocytes, a feature highly suggestive of compromised centrosome structure and function [32,33].…”
Section: Centrosomes and Senescence: Are They Related?mentioning
confidence: 99%